Complete plastome and mitogenome assembly of endangered tree Karpatiosorbus bristoliensis reveals phylogenetic architecture for Sorbus sensu lato (Rosaceae) - Li, Qiang; Wei, Ran (Frontiers in Plant Science, 2025)
IntroductionThe genus Sorbus sensu lato (Sorbus s.l.) comprises over 260 species widely distributed across temperate regions of Asia, Europe, and North America. However, hybridization and polyploidization have posed significant challenges to phylogenetic and taxonomic studies within this genus.MethodsHere, we assemble the first complete chloroplast and mitochondrial genomes of Karpatiosorbus bristoliensis to characterize organellar genomic features and establish a maternally inherited phylogenetic framework for Sorbus s.l.Results and discussionThe mitochondrial genome of K. bristoliensis is circular (386,757 bp), encoding 55 genes, including 34 protein-coding genes, 18 rRNAs, and 3 tRNAs. Its chloroplast genome has a typical quadripartite structure (160,322 bp), containing 75 protein-coding genes, 29 tRNA genes, 4 rRNA genes, and one pseudogene (ycf1Ψ). Homologous gene transfer analysis of Sorbus s.l. species revealed inter-organellar gene transfer ranging from 3,021 to 3,846 bp. RNA editing analysis revealed 274–352 editing sites in Sorbus s.l., with nad4 containing the greatest number of editing sites across all protein-coding genes except those in K. bristoliensis. Simple sequence repeat (SSR) analysis detected 48–52 SSRs per species, predominantly mononucleotide repeats. Phylogenetic reconstruction on the basis of organellar genomes revealed that Karpatiosorbus is a sister to Torminalis. Plastome-based phylogeny revealed the non-monophyletic status of Sorbus s.s., attributed to the nested placement of the hybrid-origin genera Hedlundia and Scandosorbus within the genus. Additionally, Hedlundia austriaca and H. persica should be transferred to the nothogenus Sorbomeles. Mitochondrial genome collinearity analysis revealed extensive genomic structural rearrangements. Our findings not only delineate the structural characteristics of mitochondrial genomes across Sorbus s.l. taxa but also establish a high-resolution maternal phylogenetic framework for this genus.